2020
DOI: 10.3389/fphar.2019.01566
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperpolarization-Activated Cyclic-Nucleotide-Gated Channel Blocker Ivabradine Does Not Prevent Arrhythmias in Catecholaminergic Polymorphic Ventricular Tachycardia

Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited, stressedprovoked ventricular arrhythmia. CPVT is treated by b-adrenergic receptor blockers, Na + channel inhibitors, sympathetic denervation, or by implanting a defibrillator. We showed recently that blockers of SK4 Ca 2+-activated K + channels depolarize the maximal diastolic potential, reduce the heart rate, and attenuate ventricular arrhythmias in CPVT. The aim of the present study was to examine whether the pacemaker channel inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(61 reference statements)
0
8
1
Order By: Relevance
“…Ivabradine did not prevent the arrhythmic pacing of human‐induced pluripotent stem cell–derived cardiomyocytes, nor preclude the aberrant SA nodal calcium transients in vitro. Moreover, ivabradine was unable to reduce ventricular ectopy and tachyarrhythmias in CASQ2 p.D307H transgenic mice with CPVT 21 . These findings are in contrast to the observed effects in three patients with CPVT due to genetic alterations in RYR2 (two mutations carriers, one exon 3 deletion carrier), who responded to ivabradine with suppression of ventricular ectopy and arrhythmias.…”
Section: Discussioncontrasting
confidence: 64%
“…Ivabradine did not prevent the arrhythmic pacing of human‐induced pluripotent stem cell–derived cardiomyocytes, nor preclude the aberrant SA nodal calcium transients in vitro. Moreover, ivabradine was unable to reduce ventricular ectopy and tachyarrhythmias in CASQ2 p.D307H transgenic mice with CPVT 21 . These findings are in contrast to the observed effects in three patients with CPVT due to genetic alterations in RYR2 (two mutations carriers, one exon 3 deletion carrier), who responded to ivabradine with suppression of ventricular ectopy and arrhythmias.…”
Section: Discussioncontrasting
confidence: 64%
“…However, ivabradine, similarly to β-blockers, requires dosing adjustments and has limited benefits mainly due to its specific effect on the PP interval elongation. A recent study based on an animal model of CASQ2 CPVT has shown that the decrease in the sinus rhythm provoked by ivabradine was not sufficient to improve the arrhythmic features observable with telemetric ECG recordings (Bueno-Levy et al, 2020). However, the same publication showed that SK4 blockade attenuates arrhythmic features, probably due to the AVN blockade and subsequent PR segment elongation in addition to the effect on the SAN and the PP interval.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, ivabradine was ineffective in a mouse model of catecholaminergic polymorphic ventricular tachycardia (CPVT) [ 69 ].…”
Section: Ivabradine and Ventricular Arrhythmiasmentioning
confidence: 99%
“…This in turn reduces O-linked N-acetylglucosamination of Ca 2+ -Calmodulin dependent protein kinase II and consequently reduces RyR sensitivity to Ca 2+ [ 72 ]. However, ivabradine was ineffective in the model of CPVT: it did not prevent abnormal Ca 2+ transients or arrhythmias resulting from abnormally increased RyR sensitivity in a transgenic mouse model of CPVT in vivo or in human induced pluripotent cells, exposed to isoproterenol [ 69 ].…”
Section: Ivabradine and Ventricular Arrhythmiasmentioning
confidence: 99%